ANALYSIS OF THE EFFECT OF EMPLOYEE COMPETENCY AND WORK CULTURE ON EMPLOYEE PERFORMANCE THROUGH WORK MOTIVATION AS INTERVENING VARIABLE - Dwi Ratno Nurfadilah; Sumadi -; Ni Nyoman Putu Martini (MBA - Journal of Management and Business Aplication, 2022)
The purpose of this study was to determine directly or indirectly the effect of employeecompetence and work culture on employee performance through work motivation as anintervening variable at the Bondowoso District Office. The number of samples in this study were132 respondents. The analysis technique used is the Structural Equation Model (SEM) usingWarpPLS 5.0. The results of data analysis show that the employee competence variable has asignificant effect on work motivation, work culture has a significant effect on work motivation,employee competence has a significant effect on employee performance, work culture has asignificant effect on employee performance, work motivation has a significant effect onemployee performance,Keywords: Employee Competence, Work Culture, Work Motivation and EmployeePerformance.